(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
The relationship between democratic citizenship and public schooling has been an enduring theme in U.S. educational and social theory. Among the responsibilities and the long-standing rhetorical appeal put before America’s public schools is the preparation of the Nation’s students to inherit their roles as citizens in a democracy. Historically, our American ancestors believed that a complete education was the academic nurturing of young minds as well as the development of personal integrity, character, and democratic citizenship. As the years pass, our nation becomes an increasingly diverse people, drawn from many racial, national, linguistic, and religious origins. The American cultural heritage is as diverse as our people, with multiple sources of vitality and pride. However, our political heritage is one – the vision of a common life in liberty, justice, and equality, articulated over two hundred years ago in the Declaration of Independence and the Constitution. The United States and its democracy are constantly evolving and in continuous need of citizens who can adapt its enduring traditions and values to meet these changes. The mission of social studies is to prepare students to meet that need.